Hourly, road segment-specific fossil fuel CO2 emissions for 2012 in the Los Angeles Megacity, link to ESRI shapefile - Preeti Rao; Kevin Gurney; Risa Patarasuk; Yang Song; Charles E Miller; Riley M Duren; Annmarie Eldering (PANGAEA, 2017)
We quantify hourly on-road fossil fuel carbon dioxide (FFCO2) emissions at the road segment level for the Los Angeles (LA) megacity based on observed traffic data, and characterize emission patterns across space and time. We define three different metrics to characterize FFCO2 emissions for the three road classes, and identify emissions hotspots in space and time.
Supplement to: Rao, P et al. (2017): Spatio-temporal variations in on-road CO2 emissions in the Los Angeles Megacity. AIMS Geosciences, 3(2), 239-, https://doi.org/10.3934/geosci.2017.2.239